An Assessment of Landslides Occurrence and its Implications on Local Community in Ibanda Sub County Kasese District, Uganda - Agaba, Chris (Kabale University, 2023)
This study was about landslides occurrence and its implication on local community in Ibanda Sub County, Kasese District. Thus the general objective of this study was to examine landslides occurrence and its implication on local community in Ibanda Sub County, Kasese District, Uganda. The specific objectives of the study are: to determine the main factors responsible for causing landslides; to assess the effects of landslide threat on the local community; and examine the control measures employed by farmers in landslide prone areas. This study has examined the factors causing landslides in Ibanda sub county Location targeting 120 households. A total sample of 92 farmers representing 92 households was selected. Data was presented using frequency distributed tables, bar graphs, photographs and maps from various sources. Also content analysis was analyzed using qualitative techniques. From the study findings it was established that the main factors responsible for causing landslides in Ibanda sub county Kasese district were steep gradient of slope, climate change and lack of cover vegetation. The findings revealed that, first, human activities that caused landslides include deforestation in general and removal of vegetation on slopes, specifically excavation of the toe slope, loading of the slope, defective maintenance of drainage systems, water leakages from water supply and terracing on the slopes. Second, heavy rainfall, geology, soil thickness, deep weathering, fluvial erosion of slope toe are the geomorphological factors that causes landslide in the area. Thirdly is that the socio-economic losses due to slope failures are great, ranging from destruction of infrastructure, displacement of residence, loss of property and siltation of rivers. Fourthly, the study established that farmers have adopted some responses in regard to landslides such as afforestation programmers, and adhering to warnings given by local government to re-locate to a safer ground. From the findings, the study recommends that there should be sustainable communication and education to farmers on effective ways to mitigate landslides, implementation of policies on settlements, and penalties curbing deforestation. Future researchers should investigate the influence government policies have on human activities in landslides prone areas. Keywords: Assessment, Landslides Occurrence, Implications, Local Community, Sub-County, Kasese District, Uganda.